Current investigations into magnetic nanoparticles for biomedical applications. Issue 5 (2nd February 2016) - Li, Xiaoming; Wei, Jianrong; Aifantis, Katerina E.; Fan, Yubo; Feng, Qingling; Cui, Fu‐Zhai; Watari, Fumio
Abstract: It is generally recognized that nanoparticles possess unique physicochemical properties that are largely different from those of conventional materials, specifically the electromagnetic properties of magnetic nanoparticles (MNPs). These properties have attracted many researchers to launch investigations into their potential biomedical applications, which have been reviewed in this article. First, common types of MNPs were briefly introduced. Then, the biomedical applications of MNPs were reviewed in seven parts: magnetic resonance imaging (MRI), cancer therapy, the delivery of drugs and genes, bone and dental repair, tissue engineering, biosensors, and in other aspects, which indicated that MNPs possess great potentials for many kinds of biomedical applications due to their unique properties. Although lots of achievements have been obtained, there is still a lot of work to do. New synthesis techniques and methods are still needed to develop the MNPs with satisfactory biocompatibility. More effective methods need to be exploited to prepare MNPs‐based composites with fine microstructures and high biomedical performances. Other promising research points include the development of more appropriate techniques of experiments both in vitro and in vivo to detect and analyze the biocompatibility and cytotoxicity of MNPs and understand the possible influencing mechanism of the two properties. More comprehensive investigations into the diagnostic and therapeutic applications of composites containing MNPs with "core‐shell" structure and deeper understanding and further study into the properties of MNPs to reveal their new biomedical applications, are also described in the conclusion and perspectives part. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1285–1296, 2016.